'It is important, but…': translating the Women Peace and Security (WPS) Agenda into the planning of EU peacekeeping missions*. (2nd January 2018) - Deiana, Maria-Adriana; McDonagh, Kenneth
Abstract: The European Union's commitment to mainstreaming gender in the context of peacekeeping and conflict management is expressed through a number documents and policy initiatives. However, current research highlights how EU policies and practices fall short of a commitment to take gender seriously. This paper seeks to complement these studies by examining the ways in which WPS is articulated in the planning stages of EU CSDP missions and translated into policy practices in the field. In tracking WPS as it shifts and expands into the complex institutional and operational contexts of EU peacekeeping and crisis management, we focus on two moments – the pre-deployment planning phase of operations and the post-deployment implementation phase. Our research confirms the tensions and gaps between feminist debates on gender, peace and security; the translation of feminist insights into the policy language of EU security and conflict management, and WPS as practice in the planning of CSDP operations.